Extensive Nail Changes Are a Possible Clue Indicating Multisystem Involvement in Childhood Langerhans Cell Histiocytosis: A Case Report and Literature Review - Gao, Xiaofei; Yu, Bin; Huang, Jiaotian; Yang, Haixia; Wei, Zhu (Case reports in dermatology, 2025)
Introduction: Langerhans cell histiocytosis (LCH) is a rare myeloid neoplasm that can involve nearly any organ, leading to multisystem damage. Nail involvement in LCH is particularly uncommon. Here we report a case of a young boy with multisystem LCH initially presenting with nail changes. Case Presentation: We described a boy who presented with a 2-year history of asymptomatic changes characterized by onycholysis, subungual hyperkeratosis, and purpuric striae affecting most fingernails and toenails, initially attributed to onychomycosis. Two years later, he developed multisystem involvement affecting the pituitary gland, lungs, skin, liver, and spleen. The patient succumbed shortly after histopathological confirmation via skin biopsy due to massive gastrointestinal hemorrhage secondary to cirrhosis-induced portal hypertension. Discussion: Nail lesions may serve as the initial manifestation of LCH, often preceding other characteristic disease symptoms. This early presentation provides critical diagnostic opportunities for timely intervention. Consideration of LCH, biopsy, and comprehensive evaluation of organ involvement is essential to reduce the rate of misdiagnosis and the potential for unrecognized high-risk disease. Conclusion: Nail involvement in LCH, while rare, may serve as an early clinical indicator of multisystem disease.